A systematic review of optimal planning and deployment of distributed generation and energy storage systems in power networks. (1st December 2022) - Zhang, Dong; Shafiullah, G.M.; Das, Choton K.; Wong, Kok Wai
Abstract: Climate change is encouraging a growing interest worldwide to increase renewable distributed generation (DG) integration into the power grid. DG is free from greenhouse gas emissions and can assist in mitigating the energy crisis and reducing energy costs. However, due to its variable nature and bidirectional power flows, high penetration of such DGs, particularly solar and wind, might create significant problems. Some of the issues could be related to reduced power quality, excessive power loss, and low utilization rate of power equipment. Optimal DG allocation can effectively alleviate these challenges by enhancing voltage stability, relieving the overloads of feeders, and improving the reliability of the power grid. Introducing energy storage systems (ESSs) in the network provide another possible approach to solve the above problems by stabilizing voltage and frequency. Therefore, it is essential to allocate distributed ESSs optimally on the distribution network to fully exploit their advantages. Enormous research effort has been put into these areas over the last decade by industries, utilities, and research communities. This paper presents an extensive review on the optimal planning and deployment of DGs, ESSs, and coordinated DGs and ESSs. This paper also will look at their strengths and weaknesses, the barriers to their implementation, and the associated technologies used in their implementation. Finally, this paper reviews the methods of uncertainty modelling in DG and ESS planning and their merits and drawbacks. This review includes a survey of the deployment planning approaches and investigates challenges with recommendations for future deployment. This review will be beneficial for use by utilities, researchers, investors, and stakeholders when considering the future deployment of DGs and ESSs in distribution networks to ensure a reliable and sustainable power system. Highlights: Review of optimal planning and deployment methodologies of DGs, ESSs, and coordinated DGs and ESSs Identify barriers, strengths, and weaknesses of existing research and the associated technologies used for implementation Impacts of DG integration and the need for ESS deployment are outlined. Methods of uncertainty modelling in DG and ESS planning with merits and demerits are illustrated.